2016
DOI: 10.1371/journal.pone.0164186
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Decreases TNF-α and HMGB1 Release from LPS-Stimulated Macrophages and Improves Survival in a CLP-Induced Sepsis Mice

Abstract: Naringin, a flavanone glycoside extracted from various plants, has a wide range of pharmacological effects. In the present study, we investigated naringin’s mechanism of action and its inhibitory effect on lipopolysaccharide-induced tumor necrosis factor-alpha and high-mobility group box 1 expression in macrophages, and on death in a cecal ligation and puncture induced mouse model of sepsis. Naringin increased heme oxygenase 1 expression in peritoneal macrophage cells through the activation of adenosine monoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 37 publications
2
26
0
2
Order By: Relevance
“…The protective effects of rPPE18 were, therefore, demonstrated in two models of sepsis. Ability to reduce TNF-a and attenuate organ damage in CLP-induced sepsis correlates with increased survival as has been demonstrated previously (13,14,(70)(71)(72). rPPE18 was able to consistently reduce elevated levels of TNF-a in E. coli BL21induced and CLP-induced sepsis when administered therapeutically.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The protective effects of rPPE18 were, therefore, demonstrated in two models of sepsis. Ability to reduce TNF-a and attenuate organ damage in CLP-induced sepsis correlates with increased survival as has been demonstrated previously (13,14,(70)(71)(72). rPPE18 was able to consistently reduce elevated levels of TNF-a in E. coli BL21induced and CLP-induced sepsis when administered therapeutically.…”
Section: Discussionsupporting
confidence: 75%
“…In patients with severe sepsis, anti-TNF-a Ab reduced mortality and in patients suffering from shock, there was a trend for better survival with use of anti-TNF-a Ab (12). Also, reduction in levels of TNF-a and overall inflammation correlates with increased survival in animal models of sepsis (13)(14)(15). Indeed, an exaggerated and dysregulated inflammatory response poses a challenge in sepsis and efforts need to be geared toward identifying effective anti-inflammatory agents which can reduce TNF-a and inflammation for successful resolution of sepsis (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that HMGB1 serves a critical role in the initiation of an inflammatory signaling cascade in sepsis, and that it is the most important pro-inflammatory cytokine of the lethal effect of sepsis ( 21 ). Compared with inflammatory cytokines involved in early sepsis, including TNF-α, HMGB1 is characterized by late elevated expression for a prolonged duration, providing a wide window of time for the clinical treatment of sepsis ( 22 ). As an innate immune cell, macrophages serve a crucial role in fighting against pathogenic microorganisms and initiating an immune response ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 can reach the extracellular space, once released by necrotic epithelial cells and exerts its DAMPs function or when secreted by activated innate immune cells, where it mediates potent inflammatory effects. 10,13 Macrophages and other innate immune cells actively secrete HMGB1 upon an inflammatory challenge (interleukin 1β [IL1β], lipopolysaccharide [LPS], or tumor necrosis factor α [TNFα]) in vitro and in vivo [14][15][16][17] supporting a possible role of macrophage-derived HMGB1 in tissue scarring. Recent publications documented a critical role of extracellular HMGB1 in regeneration and tissue repair processes in bone, muscle, or liver 18-21 suggesting a potential role in tissue fibrogenesis.…”
Section: Introductionmentioning
confidence: 99%